The hystero trainer, a simulator for diagnostic and operative hysteroscopy - Wallwiener, Diethelm; Rimbach, Stefan; Bastert, Gunther (The journal of the American Association of Gynecologic Laparoscopists, 1994)
Hysteroscopy has become an integral part of operative gynecology, with rates of major complications of 1%. To avoid serious, even lethal, complications, an intensive, well-structured training program for practicing surgeons is necessary. In response to these educational requirements, the Hystero Trainer was developed to provide in vitro simulation training for diagnostic and operative hysteroscopy, including laser and high-frequency electrosurgery.
Elektronische Reproduktion der Druck-Ausgabe 21. Juli 2006
Gesehen am 08.02.2024